Sesja II - Współczesna terapia chorób układu oddechowegoMethods of treatment of tuberculosis - Kołaczkowska, Małgorzata (Przewodnik Lekarza/Guide for GPs Supplement, 2008)
Tuberculosis can be cured with appropriate chemotherapy in over 90% of cases. On the basis of a large number of controlled clinical trials, treatment guidelines have been issued by international bodies such as the World Health Organization and the International Union Against Tuberculosis and Lung Disease. These guidelines have been universally accepted. Success of tuberculosis treatment depends above all on the application of the standardized treatment regimens selected by the National Tuberculosis Programmes in accordance with the regimens recommended by WHO and IUATLD (Directly Observed Treatment Short-Course). The article discusses the best recommended methods of treatment. Special attention is given to the treatment of tuberculosis: directly observed therapy, multidrug chemotherapy, adequately prolonged therapy, monitoring the efficiency of treatment with bacteriological and radiological examinations, and ensuring patient compliance.